Feeding behavior and activity period of three Neotropical bat species (Chiroptera: Phyllostomidae) on Musa paradisiaca inflorescences (Zingiberales: Musaceae) - Pedrozo, Ayesha R.; Gomes, Luiz A. C.; Uieda, Wilson [UNESP] (Fundacao Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2018)
We studied the feeding behavior and the activity period of three phyllostomid bat species on Musa paradisiaca inflorescences in an orchard located in southeastern Brazil. Glossophaga soricina (Pallas, 1766), Anoura caudifer (E. Geoffroy, 1818), and Phyllostomus discolor (Wagner, 1843) were frequently observed, videotaped, and mist-netted visiting banana inflorescences. Three approaching strategies on banana inflorescences were performed by bats: hovering (glossophagine species), upside landing (G. soricina), and downside landing (P. discolor). A new feeding behavior that consisted in hovering and licking the nectar that dripped from the distal part of a closed bract was observed for glossophagines. Visits occurred throughout the night (from 18:00 h to 05:00 h). However, activity pattern of nectarivorous bat species was significantly different from the omnivorous bat species, with the formers presenting visiting peaks at 21:00 hs and 23:30 hs, and the second at 23:45 hs and 02:30 hs. Dietary specialization, body size, and foraging behavior are important features that are linked to kind of approaching strategies to flowers and activity period of bats. Although bat visits on M. paradisiaca inflorescences are not reproductively important to banana plant, its nectar is a frequent and abundant food source for bats from the family Phyllostomidae, at least in Southeastern Brazil.
Keywords: Approaching strategies; banana flowers; nectarivorous bats; omnivorous bat; Southeastern Brazil